<u>The answer is 808/99</u>
Answer:
Independent events
Step-by-step explanation:
Given that:
Ramiro draws a marble from a jar without replacement and then flips a coin
Let
be the event that Ramiro draws a marble without replacement and;
Let
be the event of flipping a coin.
Let's have an analogy so that we can better understand the concept of independent and dependent events.
Consider a random experiment in which a marble is drawn from a jar without replacement and a fair coin is flipped together.
The event
does not in any way affect the event
of a head or a tail showing up in a flip of a coin.
Therefore, we say that
and
are independent events.
Suppose the event
affects or influence the event
, then we can say they are dependent events.
The answer is -3 because you’re plugging g(x) into f(x). For every x there is in f(x), plug in g(x)’s equation. After you get another equation (simplified), which is x^2 -7x -11, plug -1 for every x and condense.
K=8k+28
subtract 8k from both side
-7k = 28
divide both side by -7
k= -4
Hello,
h(x)'=(f(x)*g(x))'=f'(x)*g(x)+f(x)*g'(x)
h(1)=f'(1)*g(1)+(f(1)*g'(1)=-4*3+4*(-3)=-24
Answer B